The fuzzy subgroups for the abelian structure Z8 x Z2n , n > 2 (2020)
Any finite nilpotent group can be uniquely written as a direct product of p-groups. In this paper, we give explicit formulae for the number of distinct fuzzy subgroups of the cartesian product of two abelian groups of orders 2n and 8 respectively for every integer n > 2 .